Respon Pertumbuhan dan Hasil Tanaman Selada Merah (Lactuca Sativa L.) Akibat Pemberian Beberapa Konsentrasi ZPT Hantu dengan Teknologi Hidroponik Sistem Rakit Apung - Aprilia Kartika; Yustitia Akbar; Chika Sumbari (CULTIVATE: Journal of Agriculture Science, 2024)
Research in the form of a field experiment with the title "Growth Response and Yield of Red Lettuce Plants (Lactuca sativa L.) Due to the Administration of Several PGR Concentrations Using Floating Raft System Hydroponic Technology". was carried out in the experimental garden of the Faculty of Agriculture, Muhammadiyah University, West Sumatra, Tanjung Gadang Koto Village. Nan Ampek, West Payakumbuh District, Payakumbuh City, altitude ± 514 meters above sea level. The experiment lasted for 3 months, starting from June 2023 to August 2023. This experiment used a Completely Randomized Design (CRD) consisting of 5 treatments and 4 replications, in one replication there were 4 plants, 2 of which are sample plants selected randomly. The treatments were several ghost PGR concentrations of 0 ml/liter, 2 ml/liter, 4 ml/liter, 6 ml/liter and 8 ml/liter. The observation data were averaged and analyzed statistically with the F test at a significance level of 5%. Observation parameters were plant height (cm), number of leaves (strands), leaf length (cm), leaf width (cm), weight per plant (g), plant weight per plot (g), plant weight per hectare (tons). From the results of the experiments that have been carried out, it can be concluded that the administration of several concentrations of Ghost ZPT has not been able to have an effect on the growth and yield of red lettuce plants.